2005
DOI: 10.1007/s00420-004-0595-1
|View full text |Cite
|
Sign up to set email alerts
|

Dermal exposure to cyclophosphamide in hospitals during preparation, nursing and cleaning activities

Abstract: We demonstrated for the first time that actual dermal exposure to CP is common among oncology nurses working with patients treated with this anti-neoplastic drug. Pharmacy technicians and cleaning personnel, on the other hand, are potentially exposed to CP, and protection provided by gloves seemed to be sufficient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
134
2
3

Year Published

2007
2007
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(140 citation statements)
references
References 23 publications
1
134
2
3
Order By: Relevance
“…However, the duration of procedures was not documented in the current study. In a separate study, Fransman and others 9 reported an average contamination of 13.6 ng per task on the hands of pharmacy technicians (range 12.5-40.0 ng per task). In the current study, wipe samples were not collected following completion of any particular task.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…However, the duration of procedures was not documented in the current study. In a separate study, Fransman and others 9 reported an average contamination of 13.6 ng per task on the hands of pharmacy technicians (range 12.5-40.0 ng per task). In the current study, wipe samples were not collected following completion of any particular task.…”
Section: Discussionmentioning
confidence: 90%
“…This problem is notable because, although there are other routes of exposure, studies have indicated that dermal absorption is the main route of occupational exposure to antineoplastic drugs. [9][10][11][12] To the authors' knowledge, few studies have examined dermal contamination among hospital workers. In a study performed in the Netherlands, Fransman and others 13 found contamination on the hands of pharmacy technicians involved with drug preparation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies showed also that antineoplastic levels in air samples were not significantly detected, suggesting that inhalation might have a lower impact when assessing exposure (Mason et al 2005;Connor et al 2010;Huang et al 2012). Therefore, contact with contaminated workplace surfaces without gloves seems to play an important role in the dermal exposure to antineoplastic drugs (Hirst et al 1984;Sessink et al 1994;Kromhout et al 2000;Fransman et al 2005;Schierl et al 2009). In this context, most of the recently published studies give particular attention to the assessment of surfaces contamination and report a generalized contamination, even in hospitals with the best equipment and strict safety procedures (Turci et al 2003;Hedmer et al 2005;Mason et al 2005;Brouwers et al 2007;Hon et al 2011Hon et al , 2013Kopp et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…11,12 These findings are noteworthy, given that the main route of exposure to antineoplastic drugs for health care workers is through skin contact. 13,14 What remains unclear, however, are the causes of occupational exposure. Is it a lack of personal protective equipment, such as gloves, or are more systemic factors involved, such as inadequate training (e.g., not knowing proper safe handling procedures)?…”
Section: Discussionmentioning
confidence: 99%